Grow more Fuel to Grow More Food - Chaturvedi, M. D. (Indian Forester, 1950)
The pressure of population in the rich Gangetic alluvium in the Uttar Pradesh has led to the upsetting of the agronomical balance between agriculture, forestry, pastures, human habitations and communications. The low, if not diminishing, crop returns find an easy escape in the continuous extension of agriculture. The progressive encroachment of the plough on tree-lands and consequent lack of firewood have given rise to the pernicious practice of diverting the farm-yard manure from village fields to village hearths, establishing thereby a vicious circle from which there is no escape. What is needed is the restoration of a balanced rural economy providing each group of villages with its complement of cultivation pastures and tree-lands. Further extension of cultivation in this region must be viewed with the greatest concern and attention should be diverted to the creation of fuel and fodder reserves for which purpose all State lands such as those along the railways, canals, roads and waste lands unfit for cultivation must be integrated. The prevention of private forests from wanton destruction is also indicated. Even the area under cultivation should be made to support at least 2 babul trees for acre.